2021
DOI: 10.3390/v13030403
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Vector Competence Studies of Chikungunya Virus Lacking Repetitive Motifs in the 3′ Untranslated Region of the Genome

Abstract: Using reverse genetics, we analyzed a chikungunya virus (CHIKV) isolate of the Indian Ocean lineage lacking direct repeat (DR) elements in the 3′ untranslated region, namely DR1a and DR2a. While this deletion mutant CHIKV-∆DR exhibited growth characteristics comparable to the wild-type virus in Baby Hamster Kidney cells, replication of the mutant was reduced in Aedes albopictus C6/36 and Ae. aegypti Aag2 cells. Using oral and intrathoracic infection of mosquitoes, viral infectivity, dissemination, and transmis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…Viral titers of SFV, SINV, and VSV were determined by flow cytometry using anti-dsRNA antibody J2 ( Schonborn et al, 1991 ), or anti-VSV G I14 (clone 1E9F9 [ Lefrancois and Lyles, 1982 ]) combined with fluorescent secondary antibodies. Viral titers of EEEV, VEEV, MAYV, ONNV, BFV, RRV, and CHIKV were determined by plaque assay using BHK-J cells ( Karliuk et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Viral titers of SFV, SINV, and VSV were determined by flow cytometry using anti-dsRNA antibody J2 ( Schonborn et al, 1991 ), or anti-VSV G I14 (clone 1E9F9 [ Lefrancois and Lyles, 1982 ]) combined with fluorescent secondary antibodies. Viral titers of EEEV, VEEV, MAYV, ONNV, BFV, RRV, and CHIKV were determined by plaque assay using BHK-J cells ( Karliuk et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…As deletions in the CHIKV 3′ UTR are usually disadvantageous in the mosquito [ 5 , 6 , 7 , 8 , 9 ], we performed viral fitness competitions in Aedes albopictus C6/36 cells. In direct contrast to mammalian cells, the ∆44-UTR mutant virus was significantly less fit ( p < 0.0001) than the WT* CHIKV in C6/36 cells ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Within the CHIKV 3′ UTR are a series of conserved, direct repeat (DR) sequences spanning 50 to 80 nucleotides that vary in copy number across CHIKV lineages; Asian genotypes contain more DR sequences than the East/Central/South African and West African genotypes. Several studies have found that deletion of DR sequences negatively impacts CHIKV infection of mosquito cells and viral dissemination in the mosquito [ 5 , 6 , 7 , 8 , 9 , 10 ] but has minimal impacts on mammalian infection and pathogenesis [ 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this Special Issue, "Mosquito-Borne Virus Ecology", was to compile scientific data on MBVs that are currently of public health importance and the effect of ecological factors influencing the occurrence and transmission risks of these viruses. This Special Issue has some interesting contributions to science in relation to the geographical distribution of MBVs, vector competence, the effect of temperature, and mosquito vector surveillance [1][2][3][4][5][6][7][8][9][10][11]. It includes both original and review articles that provide important contributions to the scientific literature.…”
mentioning
confidence: 99%
“…The distribution of mosquito-associated viruses in West Africa was analyzed, which provides a general overview of mosquito vectors and MBVs recorded in the West African region [3]. Different studies also reported the vector competence of different mosquito vectors for certain MBVs [4,5,[9][10][11]. The competence of a mosquito vector for a particular MBV depends on the intrinsic and extrinsic characteristics of both the vector and the target virus.…”
mentioning
confidence: 99%